HOW TO UNDERSTAND AND TRANSLATE JAPANESE EXPRESSIONS IN MANGA - Eli Ningsih (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The paper presents a research about Japanese expressions in manga as one of the sources of translation study from Japanese into Indonesian language. The difficulty in doing translations of various types of Japanese expressions in the Manga  has been one of the background of research interest. The used Methodology in this research is Qualitative - Content Analysis. The result of the study shows that Manga has the level of syntactic and textual macro-level, which suggests general principles for presenting information via units such as sentence structure, i.e. syntax and combination of sentences into texts as well as pragmatic and contextual , and socio –cultural norms prevailing in the language. Examples taken from the Manga “Garasu no Kamen” (The Glass Mask) , are quoted in the analysis for each level of vocabulary learning.  The objective of the research to explore a further alternative medium of translation study in advancing the Japanese education in Indonesia.